Advantages of adipose tissue stem cells over CD34+ mobilization to decrease hepatic fibrosis in Wistar rats - De Luna Saldivar, Marcela M.; Marino Martínez, Iván Alberto; Franco Molina, Moisés Armides; Rivera Morales, Lydia Guadalupe; Alarcón Galván, Gabriela; Cordero Pérez, Paula; Rojas Martínez, Augusto; Rodríguez Padilla, Cristina; Muñoz Espinosa, Linda Elsa (2019)
Introduction and Objectives: Chronic liver inflammation may lead to hepatic cirrhosis, limiting its regenerative capacity. The clinical standard of care is transplantation, although stem cell therapy may be an alternative option. The study aim was to induce endogenous hematopoietic stem cells (HSCs) with granulocyte colony stimulating factor (G-CSF) and/or intravenous administration of adipose tissue-derived mesenchymal stem cells (MSCs) to decrease hepatic fibrosis in an experimental model.